Molecular and Clinical Investigation of COVID-19: From Pathogenesis and Immune Responses to Novel Diagnosis and Treatment - Kashani, Narjes Riahi; Azadbakht, Javid; Ehteram, Hassan; Kashani, Hamed Haddad; Rajabi-Moghadam, Hassan; Ahmad, Ejaz; Nikzad, Hossein; Hosseini, Elahe Seyed (Frontiers in Molecular Biosciences, 2022)
The coronavirus-related severe acute respiratory syndrome (SARS-CoV) in 2002/2003, the Middle East respiratory syndrome (MERS-CoV) in 2012/2013, and especially the current 2019/2021 severe acute respiratory syndrome-2 (SARS-CoV-2) negatively affected the national health systems worldwide. Different SARS-CoV-2 variants, including Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), Delta (B.1.617.2), and recently Omicron (B.1.1.529), have emerged resulting from the high rate of genetic recombination and S1-RBD/S2 mutation/deletion in the spike protein that has an impact on the virus activity. Furthermore, genetic variability in certain genes involved in the immune system might impact the level of SARS-CoV-2 recognition and immune response against the virus among different populations. Understanding the molecular mechanism and function of SARS-CoV-2 variants and their different epidemiological outcomes is a key step for effective COVID-19 treatment strategies, including antiviral drug development and vaccine designs, which can immunize people with genetic variabilities against various strains of SARS-CoV-2. In this review, we center our focus on the recent and up-to-date knowledge on SARS-CoV-2 (Alpha to Omicron) origin and evolution, structure, genetic diversity, route of transmission, pathogenesis, new diagnostic, and treatment strategies, as well as the psychological and economic impact of COVID-19 pandemic on individuals and their lives around the world.